STRATEGI BUMDES AMARTA DALAM MENGEMBANGKAN EKONOMI MASYARAKAT DESA PANDOWOHARJO TAHUN 2019 - 2020 - kemala - hayati (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2022)
AbstractThis research aims to describe BUMDes strategy in developing village economy. This research was conducted using qualitative approach studies. Data collection is conducted through interviews to informants directly as well as literature studies, data / documents from agencies and credible media both online and in print. The informants in this study numbered 5 people consisting of Director of BUMDes Amarta, Secretary of BUMDes Amarta, Partner of BUMDes Amarta, Community Leaders involved in BUMDes Amarta, and Head of Welfare Section of Pandowoharjo Village. The results of the study found strengths, weaknesses, opportunities, and threats that resulted in weight and rating found ifas and EFAS results can be known total value for IFAS is 2,952 and EFAS of 7,675 of the findings found bumdes strategy direction in developing the village economy that is aggressive strategy, based on the findings of the direction of the strategy is done matching the focus in alternative strategies using SWOT matrix to clearly describe the strategy that will be conducted BUMDes.Keywords: BUMDes, Villagers, Economic,